Student Engagement in a Large Classroom: Using Technology to Generate a Hybridized Problem-based Learning Experience in a Large First Year Undergraduate Class - Sherry Fukuzawa; Cleo Boyd (Canadian Journal for the Scholarship of Teaching and Learning, 2016)
Large first year undergraduate courses have unique challenges in the promotion of student engagement and self-directed learning due to resource constraints that prohibit small group discussions with instructors. The Monthly Virtual Mystery was developed to increase student engagement in a large (N = 725) first year undergraduate class in anthropology at the University of Toronto Mississauga. The teaching challenge was to develop a participation component (worth 6% of the final grade) that would increase student engagement without incurring any additional resource costs. The goal of the virtual mystery was to incorporate the principles of problem-based learning to engage students in self-directed learning through an online medium. Groups of approximately 50 students collaborated on a series of “virtual” case studies in a discussion board. Students submitted comments or questions each week to identify the information they needed to solve the mystery. A facilitator oversaw the discussion board to guide students in collaboration and resource acquisition. The final grades of students who participated in the virtual mystery (N=297) were compared to students who participated in a passive online learning exercise that involved watching weekly online videos and answering questions in a course reader (N = 347). Student self-selection determined group participation. Participation completion for both the virtual mystery and the course reader were high (78.8% and 91.6% respectively). There were no significant differences in the distribution of final grades between the participation options. The high completion rate of the virtual mystery demonstrated that an active learning project can be implemented using problem-based learning principles through an online discussion board; however, the large online group collaborations were problematic. Students were frustrated with repetition and inequitable participation in such large groups; however, students evaluated the monthly mystery as a valuable learning tool that engaged them through the practical nature of the case scenarios.